Gender Identity and Health-related Outcomes in a National Sample of College Students. Issue 6 (1st November 2020) - Dinger, Mary K.; Brittain, Danielle R.; Patten, Luke; Hall, Kelly C.; Burton, Steven; Hydock, David S.; Stellino, Megan B.
ABSTRACT: Background : College health education professionals need a comprehensive understanding of student health outcomes to promote health for all students. Purpose : To examine health-related outcomes by gender identity in a national sample of college students. Methods : Participants (n = 85, 912) completed the National College Health Assessment IIc during the 2017–18 academic year. Forty-seven outcomes were compared between cisgender (CG; n = 83, 425), transgender (TG; n = 1, 439), and non-binary, non-transgender (NBNT; n = 1, 048) students using separate logistic regression models and adjusting for age, race and relationship status. Results : There was a significant difference between groups for most outcomes, with TG and NBNT being more likely than CG to experience unhealthy outcomes. A similar pattern emerged for 31 of the variables, with TG and NBNT being significantly different from CG but not significantly different from each other. The greatest differences were found in the areas of drug use and mental/emotional health. Discussion : The results of this study indicate important differences in health outcomes by gender identity among college students. Translation to Health Education Practice : It is critical that health education professionals consider the unique experiences of TG and NBNT students when developing comprehensive interventions to improve their overall health status.